The Effect Of Play Therapy on Drug-taking Behavior In Toddlers In Pediatric Care Room - Masyitah Wahab; Nur Isriani Najamuddin; Niar (LPPM STIKes Muhammadiyah Ciamis, 2019)
Background: A hospitalization is an event that often causes traumatic experiences, especially in pediatric patients, namely anxiety, fear and tension or hospitalization stress. Objective: This study aims to study the effect of play therapy on drug-taking behavior in “toddler” children in the pediatric care room. Method:This study used a pre-experimental pre-test-post test one group design approach. The population of this study were toddlers (2-3 years old) taken by accidental sampling and 30 samples were obtained. Data collection uses secondary and primary data. Data analysis used univariate and bivariate analysis. Result: The results of the study were: (1) The average behavior of taking medication before playing therapy was done was 16.77; (2) The average cooperative level after playing snake and ladder therapy is 22.67 and (3) the results of the Wilcoxon Sign Rank test obtained a value of Z = -3.827 with p-value = 0.000 <0.5 meaning that there is an effect of play therapy on behavior of taking medicine while carrying out treatment for toddlers in the Asoka Room at Polewali Mandar Hospital. It Conclusion: There is an effect of playing on the acceptance of toddler age children in the act of giving oral drugs. Hospitals, as health service institutions that provide services to all levels of society, especially pediatric health services, should design and facilitate rooms that are familiar to children and prepare play facilities according to the growth and development and health conditions of children. Nurses who focus on pediatric care should pay attention to aspects of child growth and development, where toddler-aged children should apply aspects of play to achieve therapeutic goals.